2005
DOI: 10.1080/10284150500047070
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency: Differential effects on monoamine transporters

Abstract: In this study, we extend previous work on iron deficiency and dopamine (DA) transporters to include an examination of central serotonin (5-HT) and noradrenergic (NE) transporters. Rats were fed either iron deficient (ID) or iron adequate (CN) diets from weaning until adulthood. In males, an additional group of iron deficient animals (IR) were given iron supplementation. DA, 5-HT, and NE transporter binding was done in situ on thin sections. ID males, but not females, decreased DA transporter binding in the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 30 publications
4
86
1
1
Order By: Relevance
“…For instance, the basal ganglia become high in iron concentration and are more highly interconnected with REM-regulatory structures in the mesopontine tegmentum than with any other brain region (35,36). Some changes induced by early iron deficiency in the basal ganglia are not corrected with iron supplementation (2,8,9,37).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the basal ganglia become high in iron concentration and are more highly interconnected with REM-regulatory structures in the mesopontine tegmentum than with any other brain region (35,36). Some changes induced by early iron deficiency in the basal ganglia are not corrected with iron supplementation (2,8,9,37).…”
Section: Discussionmentioning
confidence: 99%
“…Other nutrients which are altered in patients with major depression and that can influence neurotransmitter production include tryptophan (and other large neutral amino acids: valine, leucine, isoleucine, phenylalanine and tyrosine) (Maes et al, 2011c, Markus, 2008, Toker et al, 2010, folic acid (Miller, 2008, Stahl, 2008, zinc , Szewczyk et al, 2011, vitamin B12 (Bottiglieri, 1996, Deana et al, 1977), vitamin B6 (Calderon-Guzman et al, 2004, Demisch and Kaczmarczyk, 1991, Hartvig et al, 1995 and iron (Baumgartner et al, 2012, Burhans et al, 2005, Coe et al, 2009). Omega-3 EFAs are also able to modify monoaminergic neurotransmission (Chalon, 2006, Su, 2009).…”
Section: Diet and Its Effect On Neurotransmittersmentioning
confidence: 99%
“…Studies in rodents have shown that iron deficiency disrupts dopaminergic signaling (Beard et al 1994;Nelson et al 1997;Erikson et al 2000Erikson et al , 2001Burhans et al 2005). This is associated with cognitive impairment potentially alleviated by psychostimulants (Mohamed et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, iron deficiency reduces the density of the dopamine transporter and the dopamine D 1 and D 2 receptors in the basal ganglia (Beard et al 1994;Nelson et al 1997;Erikson et al 2000Erikson et al , 2001Burhans et al 2005). In children, iron deficiency has been associated with motor, attentional, and memory dysfunction as well as internalizing symptoms (Lozoff et al 2000;GranthamMcGregor and Ani 2001;McCann and Ames 2007).…”
mentioning
confidence: 99%